2019
DOI: 10.1111/1365-2435.13332
|View full text |Cite
|
Sign up to set email alerts
|

The defensive function of a pollinator‐attracting floral volatile

Abstract: Benzyl acetone (4‐phenylbutan‐2‐one; BA), the dominant floral fragrance of the wild tobacco Nicotiana attenuata, is known to attract night‐time pollinators, such as Manduca sexta hawkmoths. For this pollinator, BA is not only essential for the pollen transport between conspecific plants, but also for the moth’s short‐distance handling of flowers at night. The emission of BA from the corolla limb, however, starts up to 4 hr before dusk, peaks at dusk and continues throughout the first half of the night. While t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…Among all co-expressed genes, NaIFR3 , which structurally belongs to the family of NADPH-dependent reductases 17 , showed a similar corolla limb-specific expression to both NaPAL4 and NaCHAL3 (Figure 2B). A kinetic of the transcript abundance showed that NaPAL4 , NaIFR3 and NaCHAL3 are all highly transcribed in the night (Figure 2C), which is consistent to the nocturnal floral emission of BA 6,11 .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Among all co-expressed genes, NaIFR3 , which structurally belongs to the family of NADPH-dependent reductases 17 , showed a similar corolla limb-specific expression to both NaPAL4 and NaCHAL3 (Figure 2B). A kinetic of the transcript abundance showed that NaPAL4 , NaIFR3 and NaCHAL3 are all highly transcribed in the night (Figure 2C), which is consistent to the nocturnal floral emission of BA 6,11 .…”
Section: Resultssupporting
confidence: 72%
“…Benzyl acetone (4-phenylbutan-2-one; BA), a dominant nocturnal floral volatile in the wild tobacco species Nicotiana attenuata 6,7 , is known to attract hawkmoth pollinators such as Manduca sexta for outcrossing 810 and simultaneously deter feedings from the florivore Diabrotica undecimpunctata 11 . Intriguingly, BA was not found in other Nicotiana species 12 , suggesting that BA is a species-specific floral volatile that underwent rapid evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Floral scent serves dual functions in plants, attracting beneficial visitors like pollinators and deterring antagonists such as florivores and nectar robbers (Schiestl et al 2014). In fact, a single floral volatile may act as both an attractant and deterrent, depending on its emission level and the organism receiving the signal (Galen et al 2011, Kessler et al 2019). Pollinators can also learn to associate floral volatiles with reward status and thus use floral volatile blends to select plants (Knauer and Schiestl 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Flowers in the wild tobacco Nicotiana attenuata emit benzylacetone (BA, at night to attract pollinators, such as Manduca sexta hawkmoths (Baldwin, 1997;Haverkamp et al, 2016;Euler and Baldwin, 1996), and to prevent floral damage from cucumber beetles (Kessler et al, 2019). The minor floral scent compounds are benzyl alcohol, cis-3-hexenol, and (E)--bergamotene (Kessler and Baldwin, 2007).…”
Section: Introductionmentioning
confidence: 99%